Origin and evolution of earth : research questions for a changing planet - National Research Council (U.S.). Committee on Grand Research Questions in the Solid-Earth Sciences; National Research Council (U.S.). Board on Earth Sciences and Resources; National Research Council (U.S.). Division on Earth and Life Studies; National Academies Press (U.S.) (Washington, WA National Academy Press, 2008)
Includes bibliographical references and index